Security of supply and regulation of energy networks - Jamasb, Tooraj; Pollitt, Michael (Energy policy, 2008)
In recent years, the security of energy supplies has re-emerged as a central issue in the energy policy arena in the UK and elsewhere. This re-emergence takes place against a backdrop of increased liberalisation of the energy markets, so that security of supply needs to be revisited within this context. Security of supply is multifaceted, but is often discussed in terms of physical availability of energy sources and their commodity price risk. This paper discusses the relationship between security of supply and network regulation—that is, how the energy networks, and appropriate regulation of them, can contribute to security of supply in liberalised energy sectors. Energy networks are predominantly natural monopolies and as a result are generally subject to regulatory oversight. We discuss a range of issues and trends that pose challenges and opportunities to network regulation and which call for new and innovative measures. The paper identifies a number of areas where network regulation can play a significant role in increasing the security of supply of future energy systems.